Regulation of mRNA levels by decay-promoting introns that recruit the exosome specificity factor Mmi1 - Kilchert, C; Wittmann, S; Passoni, M; Shah, S; Granneman, S; Vasiljeva, L (Cell Press, 2015)
In eukaryotic cells, inefficient splicing is surprisingly common and leads to degradation of transcripts with retained introns. How pre-mRNAs are committed to nuclear decay is unknown. Here we uncover a mechanism by which specific intron-containing transcripts are targeted for nuclear degradation in fission yeast. Sequence elements within these “decay-promoting” introns co-transcriptionally recruit the exosome specificity factor Mmi1, which induces degradation of the unspliced precursor and leads to a reduction of levels of the spliced mRNA. This mechanism negatively regulates levels of the RNA-helicase DDX5/Dbp2 to promote cell survival in response to stress. In contrast, fast removal of decay-promoting introns by co-transcriptional splicing precludes Mmi1 recruitment and relieves negative expression regulation. We propose that decay-promoting introns facilitate regulation of gene expression. Based on the identification of multiple additional Mmi1 targets including mRNAs, long non-coding RNAs, and sn/snoRNAs, we suggest a general role in RNA regulation for Mmi1 through transcript degradation.